2020
DOI: 10.3390/catal10030311
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Performance of Hierarchical MnOx/ZSM-5 Catalyst for the Low-Temperature NH3-SCR

Abstract: A ZSM-5 zeolite with a hierarchical pore structure was synthesized by the desilication-recrystallization method using tetraethyl ammonium hydroxide (TEAOH) and cetyltrimethylammonium bromide (CTAB) as the desilication and structure-directing agents, respectively. The MnO x /ZSM-5 catalyst was synthesized by the ethanol dispersion method and applied for the low-temperature selective catalytic reduction of NO x with NH 3 . The results showed that NO x conversion of the hierarchical MnO x /ZSM-5 catalyst could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…TPAOH and CTAB were used as desilicillants and structure guide agents to synthesize a ZSM-5 molecular sieve, and it was found that improved anti-SO 2 performance could be attributed to hierarchical pore structure. 33 The catalysts (FeM 0.3 O x -C, M = Nb, Ti, Mo) showed better SCR performance with the addition of CTAB, and the crystalline phase of Fe 2 O 3 was effected by adding CTAB. 34 CTAB was used for the self-assembly of Fe-ZSM-5@ Ce/mesoporous-silica, which showed higher NO x conversion, and the mesoporous silica shell promoted the dispersion of Ceria with a higher redox ability of catalysts.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…TPAOH and CTAB were used as desilicillants and structure guide agents to synthesize a ZSM-5 molecular sieve, and it was found that improved anti-SO 2 performance could be attributed to hierarchical pore structure. 33 The catalysts (FeM 0.3 O x -C, M = Nb, Ti, Mo) showed better SCR performance with the addition of CTAB, and the crystalline phase of Fe 2 O 3 was effected by adding CTAB. 34 CTAB was used for the self-assembly of Fe-ZSM-5@ Ce/mesoporous-silica, which showed higher NO x conversion, and the mesoporous silica shell promoted the dispersion of Ceria with a higher redox ability of catalysts.…”
Section: Introductionmentioning
confidence: 93%
“…This dual template played important roles in the formation of mesopores with a larger specific area and pore volume. TPAOH and CTAB were used as desilicillants and structure guide agents to synthesize a ZSM-5 molecular sieve, and it was found that improved anti-SO 2 performance could be attributed to hierarchical pore structure . The catalysts (FeM 0.3 O x -C, M = Nb, Ti, Mo) showed better SCR performance with the addition of CTAB, and the crystalline phase of Fe 2 O 3 was effected by adding CTAB .…”
Section: Introductionmentioning
confidence: 99%